Experimental Models for the Study of Central Nervous System Infection by SARS-CoV-2 - Sanclemente-Alaman, Inmaculada; Moreno-Jiménez, Lidia; Benito-Martín, María Soledad; Canales-Aguirre, Alejandro; Matías-Guiu, Jordi A.; Matías-Guiu, Jorge; Gómez-Pinedo, Ulises (Frontiers in Immunology, 2020)
Introduction. The response to the SARS-CoV-2 coronavirus epidemic requires increased research efforts to expand our knowledge of the disease. Such questions as infection rates and mechanisms, the possibility of reinfection, and potential therapeutic approaches require us not only to use the experimental models previously employed for the SARS-CoV and MERS-CoV coronaviruses, but also to generate new models to respond to urgent questions. Development. We reviewed the different experimental models used in the study of central nervous system (CNS) involvement in COVID-19, both in different cell lines that have enabled identification of the virus’ action mechanisms, and in animal models (mice, rats, hamsters, ferrets, and primates) inoculated with the virus. Specifically, we reviewed models used to assess the presence and effects of SARS-CoV-2 on the CNS, including neural cell lines, animal models such as mouse hepatitis virus CoV (especially the 59 strain), and the use of brain organoids. Conclusion. Given the clear need to increase our understanding of SARS-CoV-2, as well as its potential effects on the CNS, we must endeavor to obtain new information with cellular or animal models, with an appropriate resemblance between models and human patients.